Double-layer coated polystyrene microspheres, gold hollow foam and preparation method and application thereof

CN117700803BActive Publication Date: 2026-10-27HUAZHONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311645832.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2026-10-27
Estimated Expiration
2043-11-30

AI Technical Summary

Technical Problem

[0005]针对现有技术的以上缺陷或改进需求,本发明提供了一种双层包覆聚苯乙烯微球、双层金空壳泡沫及制备方法与应用,其目的在于解决微球制备成本高、容易引入杂质的技术问题

Benefits of technology

本发明通过改进微球的制备工艺流程,在制备期间,开始向PS微球溶液中加入K-H溶液及NaBH4溶液混合反应,由氧化还原反应置换出游离态的纳米金颗粒参与液相反应,通过逐步掺杂催化微球表面生长碳层结构,得到聚苯乙烯@碳夹心层,接着加入K-H溶液及H2O2溶液混合反应,催植种子生长包裹直至最终获得聚苯乙烯@碳夹心层@金壳双层核壳结构复合材料。该过程不需要提前单独设置纳米金颗粒制备流程,将纳米金颗粒的生成融入整个流程中,避免提前制备高浓度纳米金颗粒对原料的浪费,提高了颗粒转化利用率,降低成本,有利于实际生产应用,并且,在混合期间生成纳米金颗粒,可以避免纳米金颗粒结块以及引入杂质等问题。总体而言,该制备方法工艺简单、成本较低,金颗粒利用率高,且得到的双层包覆聚苯乙烯微球性能较好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117700803B_ABST
    Figure CN117700803B_ABST
Patent Text Reader

Abstract

The application discloses a kind of double-layer coated polystyrene microspheres, double-layer gold empty shell foam and preparation method and application, belong to micro-nano composite material technical field, the preparation method includes: with polystyrene microspheres as base core template, by modification, catalytic plant etc. Step, first in free state nano gold particle catalytic doping under formation polystyrene@carbon sandwich layer, and then the surface modification of this carbon sandwich layer, nano gold particle with inlay in carbon layer gold particle as seed induces through electrostatic adsorption effect synchronous self-assembly growth in carbon sandwich layer, until with foam form package forms polystyrene@carbon sandwich layer@gold shell double-layer core-shell structure.Further, using organic solvent tetrahydrofuran solution soaking can form double-layer gold empty shell structure.The preparation method process is simple, cost is lower, gold particle utilization rate is high, and the double-layer coated polystyrene microspheres obtained has good stability, with unique optical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of micro-nano composite material technology, and more specifically, relates to a double-layer coated polystyrene microsphere, a double-layer gold hollow foam, and their preparation methods and applications. Background Technology

[0002] Micro / nano core-shell composite materials are a class of polymer materials that can maximize the advantages of both the core and shell materials while generating a synergistic coupling effect. They exhibit superior performance compared to single-component materials in fields such as optics, electronics, and energy absorption and conversion, opening up broad market prospects for research and development in areas such as photon anomalous band absorption materials, microwave absorption materials, microelectronic components, catalysis, and biosensing. Therefore, the development of processes for the synthesis, preparation, and coating assembly of controlled metal nanoparticles has attracted widespread attention.

[0003] Currently, the growth of gold shells generally involves preparing a solution of gold nanoparticles separately, which are then attached to the surface of microspheres via electrostatic interactions to obtain gold-coated microspheres. For example, document CN109249018A discloses a self-assembly method for polystyrene microspheres coated with gold nanoparticle foam. The surface of the microsphere core is modified to carry a surface charge. A pre-prepared concentrated solution of gold nanoparticles is mixed with the modified polystyrene microsphere emulsion, allowing the gold nanoparticles to attach to the surface of the polystyrene microspheres via electrostatic interactions, resulting in polystyrene microspheres partially coated with gold nanoparticles. These microspheres are further separated and modified, then mixed again with the concentrated gold nanoparticle solution to undergo electrostatic adsorption self-assembly. This process is repeated multiple times until the gold nanoparticles form a foam-like adsorption on the surface of the polystyrene microspheres.

[0004] To ensure effective coating, the above methods require the prior preparation of a high-concentration gold nanoparticle concentrate. On one hand, the large volume of solution used for preparing the concentrate results in high production costs. Furthermore, the high concentration of gold nanoparticles in the mixed solution makes them prone to clumping, leading to low utilization and waste. On the other hand, even after coating with excess gold particles, there may still be some remaining, which can easily fall into the micro- and nano-pores of the sample, increasing cleaning difficulty. Consequently, the product will contain numerous island-like and banded impurities. During the further processing of the obtained product into devices, these impurities can spontaneously agglomerate, forming clusters and resulting in uneven distribution and other structural defects, causing difficulties for practical production applications. Summary of the Invention

[0005] In view of the above-mentioned defects or improvement needs of the existing technology, the present invention provides a double-layer coated polystyrene microsphere, a double-layer gold hollow foam, and its preparation method and application, the purpose of which is to solve the technical problems of high preparation cost and easy introduction of impurities in microspheres.

[0006] To achieve the above objectives, according to one aspect of the present invention, a method for preparing bilayer-coated polystyrene microspheres is provided, comprising: Step S1: Obtain the modified polystyrene microsphere solution, with the microspheres having a positive charge on their surface; Step S2: Mix the microsphere solution with the first group of reagents. After the reaction, a stacked carbon layer coating polystyrene microspheres is generated on the surface of the microspheres, and gold nanoparticles are embedded in the carbon layer to form a polystyrene@carbon sandwich structure. The first group of reagents includes KH solution, stabilizer and sodium borohydride solution. The KH solution contains tetrachloroauric acid and a strong base weak acid salt that inhibits the hydrolysis of tetrachloroauric acid. Step S3: Mix the polystyrene@carbon sandwich structure with the second group of reagents. After the reaction, a gold shell covering the carbon layer is grown on the surface of the carbon layer to form a polystyrene@carbon sandwich@gold shell structure. The second group of reagents includes KH solution and hydrogen peroxide solution.

[0007] In one embodiment, step S2 includes: Step S21: Mix the microsphere solution obtained in the previous step with the first group of reagents, and the reaction causes a carbon layer to be generated on the surface of the microspheres; Step S22: Centrifuge and wash the solution obtained in step S21 to obtain a microsphere emulsion; Step S23: After diluting the microsphere emulsion obtained in the previous step, add a modifier to replenish the positive charge on the surface of the microspheres, and obtain a new microsphere solution; Step S24: Mix the microsphere solution obtained in the previous step with the first group of reagents, and the reaction will cause the carbon layer to continue to grow on the surface of the microspheres; Step S25: Centrifuge and wash the solution obtained in step S24 to obtain a microsphere emulsion; Step S26: Repeat steps S23 to S25 until a carbon layer of the preset thickness is grown.

[0008] In one embodiment, step S3 includes: Step S31: Mix the microsphere solution obtained in the previous step with the second group of reagents, and the reaction is carried out by electrostatic adsorption growth using the gold nanoparticles embedded in the carbon layer as seeds. Step S32: Centrifuge and wash the solution obtained in step S31 to obtain a suspension; Step S33: After diluting the suspension obtained in the previous step, add a modifier to replenish the positive charge on the surface of the microspheres to obtain the suspension; Step S34: Mix the suspension obtained in the previous step with the second group of reagents, and the reaction allows the gold nanoparticles embedded in the carbon layer to continue to grow. Step S35: Centrifuge and wash the solution obtained in step S34 to obtain a suspension; Step S36: Repeat steps S33 to S35 until a gold shell of the preset thickness is grown.

[0009] In one embodiment, in step S2, the operation of mixing the microsphere solution with the first group of reagents includes: first mixing the microspheres with the KH solution and stabilizer in the first group of reagents and stirring evenly, and then adding the sodium borohydride solution in the first group of reagents and stirring; in step S3, the operation of mixing the polystyrene@carbon sandwich layer with the second group of reagents includes: first mixing and stirring the polystyrene@carbon sandwich layer with the KH solution in the second group of reagents, and then adding the hydrogen peroxide solution in the second group of reagents.

[0010] In one embodiment, the operation of adding the hydrogen peroxide solution includes: adding hydrogen peroxide solution until small brown particles precipitate in the solution and the solution color gradually becomes clear, at which point the addition is stopped.

[0011] In one embodiment, the thickness of the carbon layer does not exceed the particle size of the gold nanoparticles.

[0012] According to another aspect of the present invention, a double-layer coated polystyrene microsphere is provided, which is prepared by the preparation method described above.

[0013] According to another aspect of the present invention, a method for preparing a double-layer gold hollow foam is provided, which involves immersing the double-layer coated polystyrene microspheres obtained above in a tetrahydrofuran solution to dissolve the polystyrene and carbon layers, thereby forming a gold hollow foam structure.

[0014] According to another aspect of the present invention, a double-layer gold hollow foam is provided, which is prepared by the preparation method described above.

[0015] According to another aspect of the present invention, the above-described double-layer coated polystyrene microspheres or double-layer gold hollow foam are provided as optical materials.

[0016] In summary, compared with the prior art, the above-described technical solutions conceived by this invention can achieve the following beneficial effects: This invention improves the microsphere preparation process. During preparation, KH and NaBH4 solutions are added to the PS microsphere solution for a mixed reaction. A redox reaction displaces free gold nanoparticles, which participate in the liquid-phase reaction. Through gradual doping, a carbon layer structure is grown on the microsphere surface, resulting in a polystyrene@carbon sandwich layer. Then, KH and H2O2 solutions are added for a mixed reaction to promote seed growth and encapsulation until a polystyrene@carbon sandwich@gold shell double-layer core-shell composite material is finally obtained. This process eliminates the need for a separate pre-prepared gold nanoparticle preparation process, integrating the generation of gold nanoparticles into the entire process. This avoids the waste of raw materials caused by pre-preparing high-concentration gold nanoparticles, improves particle conversion and utilization, reduces costs, and is beneficial for practical production applications. Furthermore, generating gold nanoparticles during mixing avoids problems such as nanoparticle agglomeration and the introduction of impurities. Overall, this preparation method is simple, low-cost, has high gold particle utilization, and produces double-layer coated polystyrene microspheres with good performance.

[0017] Furthermore, based on the obtained double-layer coated polystyrene microspheres, the polystyrene core and carbon in the carbon sandwich layer are removed by soaking in the organic solvent tetrahydrofuran solution, forming a continuous smooth outer wall mesoporous gold particle attachment to a rough double-layer gold hollow foam material.

[0018] The structure obtained in this invention can produce new optical absorption phenomena. Characterization analysis of UV-Vis and Raman spectra during the formation of the polystyrene@carbon sandwich@gold shell shows that with repeated coating growth, the UV-Vis spectrum exhibits a flat absorption band in the near-ultraviolet range of 300-500 nm, with two absorption peaks near 345 nm and 475 nm. The peak positions gradually decrease and show a redshift trend. A flat absorption band in the visible light range of 500-1000 nm is observed, thus forming a multi-band broadband absorption range. For the Raman spectrum, polystyrene exhibits absorption at 620 cm⁻¹. -1 1000 cm -1 1220 cm -1 2900 cm -1 3060cm -1 The gradual decrease and eventual disappearance of the original characteristic peaks in the vicinity indicates a gradual process from incomplete to complete coverage of the microsphere surface by the gold shell. After soaking in tetrahydrofuran solution, a double-layered gold hollow-shell foam material is formed. The outer shell surface is continuously and densely covered, while the inner wall of the shell is rough, affecting the absorption and propagation path of light in the cavity, causing the UV-Vis absorption peaks to broaden and form a flat-band giant absorption response in the near-ultraviolet band.

[0019] Furthermore, when mixing the modified microspheres with the first group of reagents, KH solution and stabilizer were added first and stirred to ensure uniform distribution. Then sodium borohydride was added and stirred to allow the reduced gold nanoparticles to be directly adsorbed onto the surface of the microspheres, which is beneficial for embedding them during the growth of the carbon layer.

[0020] Furthermore, the thickness of the carbon layer does not exceed the particle size of the gold nanoparticles, so that the gold nanoparticles are not completely covered by the carbon layer when they are embedded in it, which is conducive to the subsequent growth of gold shells based on the embedded gold nanoparticles.

[0021] Furthermore, by adding the first group of reagents in multiple batches and replenishing the positive charge on the surface of the microspheres with each addition, the degree of reaction can be controlled and the gold particles and microspheres can always maintain effective electrostatic adsorption. This can induce the formation of a carbon layer and allow more nano-gold particles to be embedded to form a sandwich layer.

[0022] Furthermore, by adding the second group of reagents in multiple batches and replenishing the positive charge on the surface of the microspheres with each addition, the reaction rate can be controlled and the gold particles and carbon sandwich layer can be more effectively seeded and self-assembled, thereby generating gold shells with better morphology. Attached Figure Description

[0023] Figure 1 This is a flowchart of the steps in a method for preparing double-layer coated polystyrene microspheres in one embodiment; Figure 2 This is a schematic diagram of the morphological changes during the preparation of PS microspheres into a double-layered gold hollow foam in one embodiment; Figure 3 This is a particle size distribution diagram of the polystyrene microspheres prepared in Example 1; Figure 4 This is a SEM image of the carbon layer catalyzed and derived from gold nanoparticles in Example 2, attached to the surface of polystyrene microspheres. (a), (b), and (c) correspond to the microspheres after the first catalysis at 500 nm and 2 nm. 10 SEM images of the microsphere surface below, (d), (e), and (f) correspond to the microspheres after the second catalysis at 500 nm and 2 nm. 10 SEM images of the microsphere surface below, (g), (h), and (i) correspond to the microspheres after the third catalysis at 500 nm and 2 nm. 10 SEM image of the surface of the microspheres below; Figure 5 These are SEM images of the polystyrene@carbon sandwich layer outer surface seeded with gold shells in Example 3. (a), (b), and (c) correspond to the first seed growth sample with the gold shell coating at 500 nm and 360 nm. 20 SEM images of the microsphere surface, (d), (e), and (f) correspond to the second seed-grown gold-coated samples at 500 nm and 3 nm. 20 SEM images of the microsphere surface, (g), (h), and (i) correspond to the third seed growth of the gold-coated sample at 500 nm and 360 nm. 20 SEM image of the surface of the microspheres below; Figure 6 These are the thickness measurement diagrams of the gold shell, where (a), (b), and (c) correspond to the thickness of the gold shell in the first, second, and third seed growth samples. Figure 7 These are SEM images of the double-layered gold hollow-shell foam self-supporting structure formed after soaking in tetrahydrofuran solution in Example 4. (a), (b), and (c) show the structure after soaking in tetrahydrofuran aqueous solution for 24 hours at 5... 50 and 100 SEM images of the surface of the hollow gold foam shell below, (d), (e), and (f) show the surface after soaking in tetrahydrofuran aqueous solution for 48 hours at 5°C. 50 and 100 SEM images of the surface of the hollow gold foam, (g), (h), and (i) are images after soaking in tetrahydrofuran aqueous solution for 72 hours at 5°C. 50 and 100 SEM image of the surface of the hollow gold foam shell below; Figure 8 These are the spectral test images of the polystyrene@carbon sandwich layer obtained in Example 2, where (a) and (b) are the UV-Vis absorption spectrum and Raman spectrum test images, respectively; Figure 9 The images show the spectral test results of the polystyrene@carbon sandwich@gold shell double-layer core-shell structure obtained in Example 3, where (a) and (b) are the UV-Vis absorption spectrum and Raman spectrum test results, respectively. Figure 10 The UV-vis absorption spectra of the microsphere samples from Example 4 after being soaked in tetrahydrofuran for different durations are shown. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.

[0025] like Figure 1 The diagram shows the steps of a method for preparing double-layer coated polystyrene microspheres, which include: Step S1: Obtain the modified polystyrene microsphere solution, with the microspheres having a positive charge on their surface.

[0026] First, polystyrene microspheres need to be obtained. Specifically, polystyrene microsphere emulsions can be prepared using dispersion polymerization. For example, in an anhydrous ethanol environment, polyvinylpyrrolidone (PVP) is used as a stabilizer, azobisisobutyronitrile (AIBN) as an initiator, and styrene as a raw material, to polymerize and generate polystyrene microspheres. The particle size and monodispersity of the generated polystyrene microspheres will vary depending on the proportions of the reagents used.

[0027] Then, the microspheres are modified. Specifically, after obtaining a polystyrene microsphere emulsion as a substrate template, a modifier is added and stirred to functionalize and modify the surface of the microspheres, making the surface of the microspheres positively charged. For example, polyethyleneimine (PEI) can be used as a modifier. The amount of modifier can be adjusted according to the dosage of microspheres; the more microspheres there are, the more modifier is added. Taking polyethyleneimine as an example, the microsphere concentration is ( For every 0.9–1.1 g of microspheres, add 0.0025–0.003 g of polyethyleneimine. For example, take 4.5 mL of a 0.228 g / mL polystyrene microsphere (PS) emulsion in a No. 1 conical flask, add 45.5 mL of deionized water to the flask, place it on a magnetic stirrer, add 0.25 mL of 0.01 g / mL polyethyleneimine (PEI), stir for at least 1 hour, centrifuge, remove the supernatant, retain the precipitate, wash repeatedly with deionized water several times, concentrate to obtain 9 mL of modified microsphere emulsion, store in a test tube for subsequent operations.

[0028] Step S2: Mix the microsphere solution with the first group of reagents. After the reaction, a stacked carbon layer coating polystyrene microspheres is generated on the surface of the microspheres, and gold nanoparticles are embedded in the carbon layer to form a polystyrene@carbon sandwich structure. The first group of reagents includes KH solution, stabilizer and sodium borohydride solution. KH solution contains tetrachloroauric acid and a strong base weak acid salt that inhibits the hydrolysis of tetrachloroauric acid.

[0029] Experiments revealed that using sodium borohydride (NaBH4) as a reducing agent can displace gold from tetrachloroauric acid to form gold nanoparticles. These gold nanoparticles exist in a free state in solution and possess multiple attachment reaction sites, high surface activation energy, abundant charge (negative charge), and chemical catalytic properties. In this environment, free radicals or functional groups on the polystyrene surface react, catalyzing the formation of stacked carbon layers on the microsphere surface. Since the microspheres are positively charged and the gold nanoparticles are negatively charged, the gold nanoparticles are adsorbed on the microsphere surface. Therefore, during the formation of the carbon layer coating the microspheres, the gold nanoparticles are embedded in the carbon layer. In other words, a redox reaction first occurs in the liquid phase to form gold nanoparticles that are free in the solution, interacting with the microsphere surface, and the gold nanoparticles are doped and embedded in this layer to form a polystyrene@carbon sandwich layer.

[0030] In the KH solution, a weak acid-strong base salt is added as a stabilizer to prevent the hydrolysis of tetrachloroauric acid (HAuCl4•4H2O). Potassium carbonate (K2CO3) can be a suitable choice. The dosage of the weak acid-strong base salt is related to the dosage of tetrachloroauric acid when preparing the KH solution, and it is necessary to effectively inhibit the hydrolysis of tetrachloroauric acid. Taking K2CO3 as an example, when preparing the KH solution, 3 mL of HAuCl4•4H2O can be mixed with 0.05~0.06 g of K2CO3, stirred, and allowed to stand to obtain the KH solution. For example, 0.1 g of solid K2CO3 and 6 mL of HAuCl4•4H2O solution can be mixed in a black wide-mouth bottle wrapped in tin foil, water can be added and stirred for 30 min, and then placed in a refrigerator for 24 h to prepare the KH solution.

[0031] The first group of reagents includes KH solution, a stabilizer, and sodium borohydride solution. The stabilizer is used to maintain the pH value within the reaction system; trisodium citrate solution is preferred.

[0032] In one embodiment, the modified microspheres are mixed with the first group of reagents in a specific order: first, the microspheres are mixed with KH solution and stabilizer and stirred until homogeneous; then, sodium borohydride solution is added and stirred. Because the reaction between sodium borohydride and tetrachloroauric acid is rapid, if the reducing agent sodium borohydride is added first and then the oxidizing agent tetrachloroauric acid is added, or if both are added simultaneously, the tetrachloroauric acid will not be evenly dispersed in a short time. This results in a large number of displaced gold nanoparticles not having enough time to adsorb onto the surface of the microspheres and spontaneously clustering. In this embodiment, KH solution and stabilizer are added first and stirred to ensure uniform and sufficient distribution within the system, followed by the addition of sodium borohydride. Stirring allows the reduced gold nanoparticles to be directly adsorbed onto the surface of the microspheres, which is beneficial for embedding them during the growth of the carbon layer.

[0033] Because sodium borohydride undergoes a redox reaction with tetrachloroauric acid, the amount of sodium borohydride used must be sufficient to displace the gold from the tetrachloroauric acid. Specifically, in step S2, for every 1 mL of KH solution added, 0.7~0.9 mg of sodium borohydride is added. For example, for every 1 mL of KH solution added, 1 mL of 1 wt% trisodium citrate solution is added, followed by magnetic stirring and then 1 mL of 0.08 wt% NaBH4 solution is added.

[0034] Understandably, the specific amount of the first group of reagents is related to the amount of microspheres and the required thickness of the carbon layer. The more microspheres there are, the more of the first group of reagents are needed, and the thicker the required carbon layer coating will be. Specifically, it can be added in multiple batches, with a small amount of the first group of reagents added each time to control the degree of reaction. Since the positive charge on the surface of the microspheres will be neutralized during the reaction, in order to ensure that the microspheres can effectively adsorb gold nanoparticles, the positive charge on the surface of the microspheres needs to be replenished before each addition of the first group of reagents. Specifically, after each addition of the first group of reagents and sufficient reaction, impurities are removed by alternating centrifugation and washing to obtain a microsphere emulsion. Furthermore, starting from the second addition, before each addition of the first group of reagents, the microsphere emulsion is diluted and a modifier is added to replenish the positive charge on the surface of the microspheres before adding the first group of reagents. Therefore, in one embodiment, step S2 may specifically include the following sub-steps: Step S21: Mix the microsphere solution obtained in the previous step with the first group of reagents, and the reaction causes a carbon layer to be generated on the surface of the microspheres; Step S22: Centrifuge and wash the solution obtained in step S21 to obtain a microsphere emulsion; Step S23: After diluting the microsphere emulsion obtained in the previous step, add a modifier to replenish the positive charge on the surface of the microspheres, and obtain a new microsphere solution; Step S24: Mix the microsphere solution obtained in the previous step with the first group of reagents, and the reaction will cause the carbon layer to continue to grow on the surface of the microspheres; Step S25: Centrifuge and wash the solution obtained in step S24 to obtain a microsphere emulsion; Step S26: Repeat steps S23 to S25 until a carbon layer of the preset thickness is grown.

[0035] As mentioned earlier, to control the degree of reaction, the amount of the first group of reagents added each time should not be too large. In a specific embodiment, the concentration of the original polystyrene microspheres in the microsphere solution is [missing information]. At each mixing step, the first group of reagents is added according to the amount of microsphere modified concentrate. For every 0.29~0.42g, no more than 1.1mL of KH solution is added, and for every 1mL of KH solution added, 0.7~0.9mg of sodium borohydride is added. For example, after obtaining 9mL of modified microsphere emulsion in step S1, during the first mixing, 3mL of microsphere emulsion is placed in a No. 2 conical flask, 100mL of deionized water is added, along with 1mL of KH solution and 1wt% trisodium citrate solution. After magnetic stirring, 1mL of 0.08wt% NaBH4 solution is added, and magnetic stirring continues to ensure complete reaction. After each reaction, a modifier is added to replenish the positive charge on the surface of the microspheres, and then impurities are removed by centrifugation and washing to obtain 9mL of microsphere emulsion. Before the next mixing, dilute the resulting 9 mL microsphere emulsion with 100 mL of deionized water. Then, add 1 mL of KH solution and 1 wt% trisodium citrate solution and stir. Next, add 1 mL of 0.08 wt% NaBH4 solution and continue magnetic stirring to ensure a complete reaction. Repeat the above process until a carbon layer of the predetermined thickness is formed, resulting in microspheres with a polystyrene@carbon sandwich structure.

[0036] In one embodiment, to prevent the gold nanoparticles from being completely encapsulated by the carbon layer when embedded, thus facilitating the subsequent growth of a gold shell based on the embedded gold nanoparticles, the thickness of the carbon layer generally does not exceed the particle size of the gold nanoparticles. In one embodiment, the particle size of the gold nanoparticles ranges from 2 to 3 nm.

[0037] Step S3: Mix the polystyrene@carbon sandwich structure with the second group of reagents. After the reaction, a gold shell covering the carbon layer is grown on the surface of the carbon layer to form a polystyrene@carbon sandwich@gold shell structure. The second group of reagents includes KH solution and hydrogen peroxide solution.

[0038] In this step, hydrogen peroxide was chosen as the reducing agent. Experiments showed that hydrogen peroxide, as a reducing agent, can undergo a redox reaction with tetrachloroauric acid to displace gold nanoparticles without affecting the carbon sandwich layer. While the tetrachloroauric acid and hydrogen peroxide react to displace the gold nanoparticles, the excess negative charge on the surface of the gold nanoparticles and the positive charge on the surface of the microspheres are fully conjugated and absorbed. The gold particles couple with the carbon sandwich layer, inducing seed growth by embedding the gold nanoparticles within the carbon sandwich layer on the microsphere surface. This alters the distribution pattern of the gold particles embedded on the surface of the carbon sandwich layer, resulting in an uneven and rugged structure. This, in turn, induces conjugation during seed growth, leading to anisotropic growth of the shell layer and differentiation. Macroscopically, this manifests as a gradual change in the shell surface morphology from granular to needle-like and finally to a flaky structure. Ultimately, the gold nanoparticles, through electrostatic interaction, form a continuous foam-like shell structure covering the carbon sandwich layer, creating a polystyrene@carbon sandwich@gold shell double-layer core-shell structure material with a shell thickness of approximately 23-72 nm.

[0039] In one embodiment, the operation of mixing the polystyrene@carbon sandwich structure with the second group of reagents includes: first mixing and stirring the polystyrene@carbon sandwich structure with the KH solution in the second group of reagents, and then adding the hydrogen peroxide solution in the second group of reagents, for the same reason as adding the first group of reagents in sequence in step S2.

[0040] In one embodiment, since the redox reaction between hydrogen peroxide and tetrachloroauric acid is very rapid, a hydrogen peroxide solution with a mass fraction of 0.08-0.12 mol / L is added at equal intervals of 10-20 seconds until small brown particles precipitate out of the solution and the solution gradually becomes clear. At this point, it indicates that the amount of hydrogen peroxide is sufficient, and the addition is stopped. The mixture is then stirred to allow the reaction to proceed fully.

[0041] Understandably, the specific amount of KH solution used is related to the amount of polystyrene@carbon sandwich layer used; the more polystyrene@carbon sandwich layer used, the more KH solution is needed. Specifically, it can be added in multiple batches, with a small amount of the second group of reagents added each time to control the reaction rate. Since the positive charge on the surface of the microspheres will be neutralized during the reaction, in order to ensure that the microspheres can effectively adsorb gold nanoparticles, the positive charge on the surface of the microspheres needs to be replenished before each addition of the second group of reagents. Specifically, after each addition of the second group of reagents and sufficient reaction, impurities are removed by alternating centrifugation and washing to obtain a microsphere emulsion. Furthermore, starting from the second time, before each addition of the second group of reagents, the microsphere emulsion is diluted and a modifier is added to replenish the positive charge on the surface of the microspheres before adding the second group of reagents. Therefore, in one embodiment, step S3 may specifically include the following sub-steps: Step S31: Mix the microsphere solution obtained in the previous step with the second group of reagents, and react to allow the gold nanoparticles embedded in the carbon layer to grow. Step S32: Centrifuge and wash the solution obtained in step S31 to obtain a suspension; Step S33: After diluting the precipitate obtained in the previous step, add a modifier to replenish the positive charge on the surface of the microspheres to obtain a suspension; Step S34: Mix the suspension obtained in the previous step with the second group of reagents, and the reaction allows the gold nanoparticles embedded in the carbon layer to continue to grow. Step S35: Centrifuge and wash the solution obtained in step S34 to obtain a suspension; Step S36: Repeat steps S33 to S35 until a gold shell of the preset thickness is grown.

[0042] As mentioned earlier, to control the degree of reaction, the amount of the second group of reagents added each time should not be excessive. In a specific embodiment, the concentration of the original polystyrene microspheres in the suspension is controlled at [specific value] during each mixing. Add KH solution at a concentration of g / mL, based on the amount of polystyrene microspheres. For every 0.097~0.14g of polystyrene microspheres, add no more than 2.2mL of KH solution. Then, add hydrogen peroxide solution with a mass fraction of 0.08~0.12mol / L at intervals until small brown particles precipitate in the solution and the solution gradually becomes clear. For example, after obtaining 10mL of microsphere emulsion in the last operation in step S1, during the first mixing, take 3mL of the microsphere emulsion and dilute it with 150mL of deionized water, add 2mL of KH solution, stir magnetically, and then use 200... Add 0.1 mol / L H₂O₂ every 20 seconds using a 200L pipette until small brown particles precipitate and the solution gradually becomes clear. Stop adding H₂O₂ and continue stirring to ensure complete reaction. After each reaction, add a modifier to replenish the positive charge on the microsphere surface, then remove impurities by centrifugation and washing to obtain 10 mL of microsphere emulsion. Before the next mixing, dilute the 10 mL microsphere emulsion with 150 mL of deionized water, then add 2 mL of KH solution, stir magnetically, and then add 0.1 mol / L H₂O₂ every 20 seconds using a 200L pipette until small brown particles precipitate and the solution gradually becomes clear. Stop adding H₂O₂ and continue stirring to ensure complete reaction. Repeat the above process, gradually increasing the gold shell thickness until the preset thickness is reached, resulting in the final polystyrene@carbon sandwich@gold shell structure.

[0043] This invention also relates to a double-layered polystyrene microsphere prepared by the method described above. Specifically, the emulsion containing the double-layered polystyrene microspheres obtained above can be subjected to solid-liquid separation, washing, and drying to obtain microsphere powder.

[0044] The present invention also relates to a method for preparing a double-layer gold hollow foam, which includes: immersing the obtained double-layer coated polystyrene microspheres in a tetrahydrofuran solution to dissolve the polystyrene and carbon layer, thereby forming a gold hollow foam structure.

[0045] Preferably, to ensure the polystyrene core and its surface sandwich carbon layer are fully dissolved, the volume ratio of tetrahydrofuran to deionized water is 3:1, and the soaking time is 72 hours.

[0046] Specifically, soaking in a mixed solution of the organic solvent tetrahydrofuran and deionized water requires controlling the volume ratio of tetrahydrofuran to deionized water and the reaction time. After removing the core polystyrene and its surface carbon sandwich layer through soaking, the carbon layer completely dissolves in the tetrahydrofuran solution, while the gold nanoparticles embedded in the carbon layer are insoluble in the tetrahydrofuran solution. As a result, they adhere to the inner wall of the outer shell, forming a double-layer gold hollow foam structure material with a rough inner wall. It should be noted that tetrahydrofuran is toxic and volatile and may produce an irritating odor, so it must be handled in a fume hood according to regulations.

[0047] This invention uses polystyrene (PS) as a template and, through the catalysis of free-state gold nanoparticles, catalyzes the formation of a carbon sandwich layer on the surface of microspheres. This layer is then used as an intermediate to further encapsulate and form a gold shell through seed growth. Immersion then forms a hollow gold sphere shell, altering the spatial topology of the gold nanoparticles. Consequently, the size, shape, and dielectric constants of the inner and outer shells interact with each other, resulting in more significant resonant absorption characteristics. Furthermore, due to the different structures of the inner and outer walls of the shell, the light absorption modes differ between the outer and inner surfaces. On the outer surface, the absorption is related to the shell thickness; inside, the interaction with the inner sidewalls causes multiple reflections and refractions, thus primarily depending on the shell radius and the propagation path within the shell.

[0048] This invention also relates to a double-layer gold hollow foam prepared by the double-layer gold hollow foam preparation method described above.

[0049] The double-layer gold foam structure obtained by this invention has a dense outer surface of gold shell, which reduces the scattering and reflection modes of light and makes its absorption intensity higher, while the rough inner wall of the shell can provide more active sites to increase the light absorption efficiency. It has more surface states and interface effects, which affect the absorption and propagation path of light in the cavity, thereby broadening the absorption peak position to form a near-ultraviolet band flat-band response giant absorption.

[0050] like Figure 2 The diagram shows the morphological changes during the preparation of PS microspheres into double-layer gold hollow foam. This invention can obtain double-layer coated polystyrene microspheres and can further obtain double-layer gold hollow foam.

[0051] The preparation method described above will be explained in detail below through specific examples.

[0052] Example 1 (1-1) Preparation of 6.18 m polystyrene (PS) microsphere emulsion (1) Weigh 0.8406g of polyvinylpyrrolidone (PVP) powder onto filter paper, pour it into a 10mL test tube, and inject 5mL of anhydrous ethanol into the test tube; weigh 0.4511g of azobisisobutyronitrile (AIBN) powder onto filter paper, pour it into another 10mL test tube, and inject 5mL of styrene into the other test tube. Sonicate both test tubes for about 5min at a water temperature of 40℃. (2) Fix the three-necked flask on a heat-collecting constant temperature magnetic stirrer, and control the height of the stirring rod at 0.8-1.2cm without touching the bottom of the flask; (3) Transfer the solution in the two test tubes in (1) to the solution in the three-necked flask. After the transfer, the test tubes need to be rinsed with the original solvent once to reduce the residue of the drug solution. The rinsing solution is transferred from the side opening of the three-necked flask. The final reaction environment contains 100 mL of anhydrous ethanol and 47 mL of styrene. Attach stopcocks to both openings of the flask. (4) Connect a nitrogen bag to the gas valve at the piston port on one side of the three-necked flask. Use the vacuum testing device to check the air tightness on the other side. Repeat the vacuuming and filling process 3 times to fill the flask with nitrogen. Close the gas valve at the interface of the vacuum testing device and keep the gas valve at the nitrogen bag connection open. (5) Adjust the motor speed to about 120 rpm (±2 rpm), start the constant temperature water bath to heat and control the temperature at 70 ℃. The water in the bath should submerge the solution in the three-necked flask. A plastic film should be placed around the water bath to slow down the evaporation rate. The reaction should last for 24 hours. (6) After the reaction is complete, wash and separate the sample. Centrifuge the sample at 3000 rpm in a centrifuge. Take out the precipitate and wash it three times each with anhydrous ethanol and deionized water. Finally, concentrate and store it in a 10 mL test tube to obtain polystyrene microsphere emulsion for later use.

[0053] like Figure 3 The image shows the particle size distribution of the polystyrene microspheres prepared in Example 1. It can be seen that it approximates a Gaussian distribution, indicating good monodispersity of the microsphere sample, with an average size of approximately 6.18. m, dispersion coefficient ε It is approximately 0.118.

[0054] Example 2 (2-1) Modified PS microsphere emulsion (1) Take the PS microsphere emulsion from Example 1 and repeatedly sonicate, centrifuge, and wash it with deionized water and anhydrous ethanol to make it monodisperse; (2) The concentration of the prepared PS emulsion was calculated to be 0.228 g / mL; (3) Take 4.5 mL of PS emulsion with a concentration of 0.228 g / mL into a No. 1 conical flask, add 45.5 mL of deionized water into the conical flask, place it on a magnetic stirrer, add 0.25 mL of polyethyleneimine (PEI) with a concentration of 0.01 g / mL, and stir for no less than 1 h; (4) Centrifuge to remove the upper liquid and retain the lower precipitate. Wash repeatedly with deionized water several times. After washing, concentrate to obtain 9 mL of modified microsphere emulsion and store it in a test tube.

[0055] (2-2) Fostering carbon sandwich structure (1) Preliminary experiment: Take 0.1g K2CO3 solid and 6mL HAuCl4•4H2O solution and mix them in a black wide-mouth bottle wrapped with tin foil. Add water and stir magnetically for 30min. Place it in the refrigerator for 24h to prepare KH solution. (2) Take 0.2762g of trisodium citrate solid and 24mL of deionized water in a small beaker and stir magnetically for 5min to prepare a 1wt% trisodium citrate solution; (3) Take 0.0156g of NaBH4 solid into a small beaker, add 20mL of deionized water, stir magnetically for about 1min, and prepare a NaBH4 solution with a mass fraction of 0.08wt%. (4) Take 3 mL of the modified PS microsphere emulsion obtained in (2-1) and place it in Erlenmeyer flask No. 2. Add 100 mL of deionized water, 1 mL of KH solution and 1 wt% trisodium citrate solution to Erlenmeyer flask No. 2 and stir magnetically for about 10 min. (5) Add 1 mL of 0.08 wt% NaBH4 solution to (4) and stir magnetically for 30 min; (6) Centrifuge the sample solution after reaction in (5) alternately, wash it 3 times, and finally concentrate it into a 10mL test tube. Let it stand to form a precipitate, which is the first modification catalysis. (7) Add 50 mL of deionized water to a No. 3 conical flask, dissolve the lower precipitate of (6) in deionized water, transfer it into the conical flask, add 0.25 mL of PEI with a concentration of 0.01 g / mL, and stir for at least 1 h; (8) Centrifuge and wash the suspension in (7) 6 times, and concentrate it to 3 mL; (9) Transfer the sample from (8) to Erlenmeyer flask No. 4, add 100 mL of deionized water, 1 mL of KH solution and 1 wt% trisodium citrate solution to Erlenmeyer flask No. 4, and stir magnetically for about 10 min. (10) Take 1 mL of 0.08 wt% NaBH4 solution and add it to (9), and stir magnetically for 30 min; (11) Centrifuge the sample solution after reaction in (10) alternately, wash it 3 times, and finally concentrate it into a 10mL test tube. Let it stand to form a precipitate, which is the secondary modified catalyst. (12) Add 50 mL of deionized water to a No. 5 conical flask, dissolve the lower layer precipitate from (11) in deionized water, transfer it to the conical flask, add 0.25 mL of PEI with a concentration of 0.01 g / mL, and stir for at least 1 h; (13) Take out the suspension in (12), centrifuge, wash 6 times, and concentrate to 3 mL; (14) Add 100 mL of deionized water to the No. 6 conical flask, then transfer the sample from (13) to the conical flask, add 1 mL of KH solution and 1 wt% trisodium citrate solution, and stir magnetically for about 10 min. (15) Take 1 mL of 0.08 wt% NaBH4 solution and add it to (14), and stir magnetically for 30 min; (16) After the reaction in (15), the sample solution is centrifuged and washed three times alternately, and finally concentrated into a 10mL test tube, which is the three-stage modified catalyst.

[0056] like Figure 4 The image shown is a SEM image of a carbon layer catalyzed by gold nanoparticles and attached to the surface of polystyrene microspheres in Example 2. (a), (b), and (c) correspond to the microspheres after the first catalysis at 500 nm and 2 nm. 10 SEM images of the microsphere surface below, (d), (e), and (f) correspond to the microspheres after the second catalysis at 500 nm and 2 nm. 10 SEM images of the microsphere surface below, (g), (h), and (i) correspond to the microspheres after the third catalysis at 500 nm and 2 nm. 10 The image below shows a SEM image of the microsphere surface. It can be seen that as the reaction proceeds, a layered structure doped with gold particles gradually forms on the microsphere surface.

[0057] like Figure 8The image shows the spectral distribution of the polystyrene@carbon sandwich layer obtained in Example 2. (a) and (b) are the UV-Vis and Raman spectra, respectively. From top to bottom, the catalytic modification is represented by 1, 2, and 3 catalytic cycles. Compared to the control group, with increasing catalytic modification cycles, (a) shows that the experimental group exhibits weakening fluctuations in the 700-1000 nm range, a wave packet forming in the 500-600 nm range with gradually increasing half-peak width, and bimodal absorption in the 200-300 nm UV absorption band. The characteristic absorption peaks gradually decrease and show a redshift trend. (b) shows that due to the formation of the carbon sandwich layer on the microsphere surface, Bragg scattering occurs between light and the layer surface, forming a localized narrow band at 1600 cm⁻¹. -1 The area widened, and a carbon layer appeared at 1580 cm. -1 Characteristic peak positions of the left and right (G peak).

[0058] Example 3 (3-1) Promote the growth of golden shell (1) Add 150 mL of deionized water to a clean and dried No. 7 conical flask, take 3 mL of the modified catalytic mixture from Example (2-2), add 2 mL of KH solution, and stir magnetically for about 10 min; (2) Add 200 ml of water to the No. 7 conical flask. Add 0.1 mol / L H2O2 to the L pipette every 20 seconds until small brown particles precipitate out of the solution and the solution gradually becomes clear. Stop adding H2O2, stir for about 3 hours, and let it stand for 24 hours to precipitate. (3) Take out the precipitate from (2), centrifuge and wash 3 times to obtain a seed growth gold shell sample; (4) Add 50 mL of deionized water to a No. 8 conical flask, transfer the precipitate from (3) to the conical flask, add 0.25 mL of PEI with a concentration of 0.01 g / mL, and stir for 3 h; (5) Take out the suspension in (4), centrifuge and wash 6 times, concentrate it into a 10mL test tube and let it stand to precipitate; (6) Add 150 mL of deionized water to a No. 9 conical flask, transfer the precipitate from (5) to the conical flask, add 2 mL of K-H solution, stir magnetically for about 10 min, and repeat step (2). (7) Take out the precipitate from (6), centrifuge and wash 3 times to obtain the secondary seed growth coated gold shell sample; (8) Transfer the precipitate from (7) to a No. 10 conical flask, add 50 mL of deionized water and 0.25 mL of PEI with a concentration of 0.01 g / mL, and stir for 3 h; (9) Take 150 mL of deionized water into the No. 11 conical flask, transfer the precipitate in (8) into the conical flask, add 2 mL of KH solution, stir magnetically for about 10 min, and repeat step (2) again. (10) Take out the precipitate from (9), centrifuge and wash 3 times to obtain the three seed growth coated gold shell samples.

[0059] like Figure 5 The image shown is a SEM image of the gold-coated polystyrene@carbon sandwich layer in Example 3, where (a), (b), and (c) correspond to the first seed growth sample with the gold-coated layer at 500 nm and 360 nm. 20 SEM images of the microsphere surface, (d), (e), and (f) correspond to the second seed-grown gold-coated samples at 500 nm and 3 nm. 20 SEM images of the microsphere surface, (g), (h), and (i) correspond to the third seed growth of the gold-coated sample at 500 nm and 360 nm. 20 The image shows a SEM image of the microsphere surface. It reveals a step-by-step, multi-stage growth process where the outer shell wall transforms from granular to needle-like structures and then to scale-like forms.

[0060] like Figure 6 The figure shows the thickness measurement of the gold shell. (a), (b), and (c) correspond to the thickness of the gold shell in the first, second, and third seed growth samples. The average thickness of the gold shell in the first sample was 24 nm, the average thickness in the second sample was 51 nm, and the average thickness in the third sample was 72 nm.

[0061] like Figure 9 The image shows the spectral test results of the polystyrene@carbon sandwich@gold double-layer core-shell structure obtained in Example 3. (a) and (b) are the UV-Vis and Raman spectra, respectively. The three curves in the figure represent the first, second, and third coating cycles from top to bottom. With increasing seed growth cycles, the UV-Vis spectrum shows a flat absorption band in the near-ultraviolet range of 300-500 nm, with two absorption peaks near 345 nm and 475 nm. The peak positions gradually decrease and show a redshift trend. A flat absorption band in the visible light range of 500-1000 nm is observed, thus forming a multi-band broadband absorption range. For the Raman spectrum, polystyrene shows a peak at 620 cm⁻¹. -1 1000 cm -1 1220 cm -1 2900 cm -1 3060cm -1 The gradual decrease and eventual disappearance of the original characteristic peaks in the vicinity indicates a gradual process of the gold shell covering the surface of the microspheres from incomplete to complete.

[0062] Example 4 (4-1) Obtaining Gold Bubbles (1) Place the sample from Example 3 into a sample bottle and put it in a fume hood; (2) Using a 5mL pipette, pipette 30mL of tetrahydrofuran into a beaker, then add an equal volume of deionized water. Prepare a tetrahydrofuran aqueous solution at a volume ratio of 3:1, stir well, and set aside. The densities of tetrahydrofuran and water are 0.89 g / cm³. 3 and 1.02 g / cm 3 The mass fraction of the tetrahydrofuran aqueous solution can be calculated to be 72.8 wt%. (3) Select three clean small sample bottles respectively, add 40 mL of tetrahydrofuran aqueous solution to each small sample bottle, and soak the sample precipitate obtained by catalytic growth of gold shell in Example 3 for 24h, 48h and 72h respectively. (4) After the soaking time is over, the clear liquid in the upper layer of the sample bottle is drawn into the waste liquid pool. The remaining solution and precipitate are added with an appropriate amount of deionized water, and the mixture is repeatedly centrifuged and washed. Finally, it is placed in a forced-air drying oven and dried at 65 °C to obtain a double-layer gold hollow foam structure material.

[0063] like Figure 7 The image shown is a SEM image of the double-layer gold hollow foam self-supporting structure formed after soaking in tetrahydrofuran solution in Example 4. (a), (b), and (c) are images of the structure after soaking in tetrahydrofuran aqueous solution for 24 hours at 5°C. 50 and 100 SEM images of the surface of the hollow gold foam shell below, (d), (e), and (f) show the surface after soaking in tetrahydrofuran aqueous solution for 48 hours at 5°C. 50 and 100 SEM images of the surface of the hollow gold foam, (g), (h), and (i) are images after soaking in tetrahydrofuran aqueous solution for 72 hours at 5°C. 50 and 100 The image shows a SEM image of the surface of the hollow gold foam. It can be seen that the hollow structure remains stable under a wide field of view.

[0064] like Figure 10 The image shows the UV-Vis absorption spectra of the microsphere samples after immersion in tetrahydrofuran for different durations. The three curves in the figure, from top to bottom, represent the flat-response giant absorption characteristics of the double-layered gold hollow foam in the near-ultraviolet band of 300-500 nm after immersion in tetrahydrofuran aqueous solution for 24 h, 48 h, and 72 h, respectively.

[0065] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing double-layer coated polystyrene microspheres, characterized in that, include: Step S1: Obtain the modified polystyrene microsphere solution, with the microspheres having a positive charge on their surface; Step S2: Mix the microsphere solution with the first group of reagents. After the reaction, a stacked carbon layer coating polystyrene microspheres is generated on the surface of the microspheres, and gold nanoparticles are embedded in the carbon layer to form a polystyrene@carbon sandwich structure. The first group of reagents includes KH solution, stabilizer and sodium borohydride solution. The KH solution contains tetrachloroauric acid and a strong base weak acid salt that inhibits the hydrolysis of tetrachloroauric acid. Step S3: Mix the polystyrene@carbon sandwich structure with the second group of reagents. After the reaction, a gold shell covering the carbon layer is grown on the surface of the carbon layer to form a polystyrene@carbon sandwich@gold shell structure. The second group of reagents includes KH solution and hydrogen peroxide solution.

2. The preparation method according to claim 1, characterized in that, Step S2 includes: Step S21: Mix the microsphere solution obtained in step S1 with the first group of reagents, and the reaction causes a carbon layer to be generated on the surface of the microspheres; Step S22: Centrifuge and wash the solution obtained in step S21 to obtain a microsphere emulsion; Step S23: After diluting the microsphere emulsion obtained in step S22, add a modifier to replenish the positive charge on the surface of the microspheres to obtain a new microsphere solution; Step S24: Mix the microsphere solution obtained in step S23 with the first group of reagents, and the reaction will cause the carbon layer to continue to grow on the surface of the microspheres; Step S25: Centrifuge and wash the solution obtained in step S24 to obtain a microsphere emulsion; Step S26: Repeat steps S23 to S25 until a carbon layer of the preset thickness is grown.

3. The preparation method according to claim 1, characterized in that, Step S3 includes: Step S31: Mix the polystyrene@carbon sandwich structure obtained in step S2 with the second group of reagents, and the reaction is carried out by electrostatic adsorption growth using gold nanoparticles embedded in the carbon layer as seeds. Step S32: Centrifuge and wash the solution obtained in step S31 to obtain a suspension; Step S33: After diluting the suspension obtained in step S32, add a modifier to replenish the positive charge on the surface of the microspheres to obtain the suspension. Step S34: Mix the suspension obtained in step S33 with the second group of reagents, and the reaction allows the gold nanoparticles embedded in the carbon layer to continue to grow. Step S35: Centrifuge and wash the solution obtained in step S34 to obtain a suspension; Step S36: Repeat steps S33 to S35 until a gold shell of the preset thickness is grown.

4. The preparation method according to claim 1, characterized in that, In step S2, the operation of mixing the microsphere solution with the first group of reagents includes: first mixing the microspheres with the KH solution and stabilizer in the first group of reagents and stirring evenly, then adding the sodium borohydride solution in the first group of reagents and stirring. In step S3, the operation of mixing the polystyrene@carbon sandwich layer with the second group of reagents includes: first mixing and stirring the polystyrene@carbon sandwich layer with the KH solution in the second group of reagents, and then adding the hydrogen peroxide solution in the second group of reagents.

5. The preparation method according to claim 1, characterized in that, In step S3, the operation of adding the hydrogen peroxide solution includes: adding hydrogen peroxide solution until small brown particles precipitate in the solution and the solution color gradually becomes clear, then stopping the addition.

6. The preparation method according to claim 1, characterized in that, The thickness of the carbon layer does not exceed the particle size of the gold nanoparticles.

7. A double-layer coated polystyrene microsphere, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 6.

8. A method for preparing a double-layer gold hollow foam, characterized in that, include: The double-layer coated polystyrene microspheres of claim 7 are immersed in a tetrahydrofuran solution to dissolve the polystyrene and carbon layer, forming a gold hollow foam structure.

9. A double-layered gold hollow foam, characterized in that, It is prepared by the preparation method described in claim 8.

10. The application of a double-layered polystyrene microsphere as described in claim 7 or a double-layered gold hollow foam as described in claim 9 as an optical material.

Citation Information

Patent Citations

  • Gold nanoparticle foam coated polystyrene microsphere self-assembly method

    CN109249018A